Análisis de vulnerabilidad física – estructural ante la amenaza de deslizamiento en la comunidad de Apahua, parroquia rural Salinas, cantón Guaranda. Período mayo-septiembre 2023. - Corro Caiza, Haminton Alfonso (2023)
The present research project called “Analysis of structural physical vulnerability to the threat of landslides in the community of Apahua, rural parish, Salinas, Guaranda canton, had the purpose of identifying the areas susceptible to landslides that affect the road system, to propose measures and mitigation actions against the occurrence of landslides For the investigation, the independent variable Physical-structural was determined, within which the pathologies of the structural system were evaluated, for which the methodology for structural and pathological monitoring of homes affected by landslides was used, through a Technical Evaluation Sheet. Mora Vahrson's methodology made it possible to identify areas susceptible to landslides; for this it was necessary to use geographic information systems (ArcMap), weighing the triggering and conditioning factors. According to the results obtained, it was determined that the susceptible areas have a high level, whose correlation was established between the level of threat and vulnerability. Key Words: Algebra of Maps, Landslides, Pathology and Structural System